Krisis Pencemaran Minyak Hitam [Sludge Oil] Merugikan Masyarakat Kepulauan: Bukti Dari Pulau Bintan. - Suyito Suyito; Haji Mustakim; Yessy Alvianti Dev; Linayati Lestari; Alpino Susanto (Asosiasi Ide Bahasa Kepri, 2025)
A study on the black oil pollution crisis [Sludge Oil] is detrimental to the island community, a proof from the island of Bintan that occurs and continues every year. This study contributes to a deep understanding that the black oil pollution crisis [Sludge Oil] in Bintan is not a trouble, but has become an issue in the theoretical context. So this is not just a regional problem, but has concerned a national issue about this black oil waste crisis. This study focuses on an argument question: